Expanding Generally Equipment Effectiveness by Execution of TPM to Lessening Misfortunes (International Journal of Innovative Research in Computer Science & Technology, 2020)
Most prevalent and well-liked techniques  are those that measure the overall effectiveness of the  device. Total productive maintenance is a frequent  strategy utilized. In this project, we'll use TPM to  compute OEE and work through issues specific to a  chosen industry. We gather machine shop data from the  various industries, and after that, we determine the  maximum OEE. The ideal OEE value is around 96%.
Keywords: Total Productive Maintenance; TPM; OEE; TQM